Electronic Equipment Loads Telemetry in Ferry Ship Passenger Room Based on Long Range Wireless Communication (LoRA) - Aldian Dwi Pamungkas; Lilik Subiyanto; Afif Zuhri Arfianto; Hendra Agus Widodo; Rachmad Andri Atmoko (Future Science, 2020)
The development of information technology both software and hardware support development in various fields, especially in the field of electronics. This progress can be used in making automation systems and controlling electronic and electrical components. With the increasing need for system monitoring in real-time, a model that is more than just portable storage can be developed, using telemetry (remote measurement) systems. This research makes a prototype that is used for remote monitoring of electronic equip-ment telemetry in the passenger space of ferries using wireless communica-tions. Radiofrequency is used for electronic equipment located in the passen-ger space. The system is made using ACS 712 current sensor and ZMPT 101B voltage sensor to measure current and voltage monitored by long-range wire-less communications (LoRa) to maintain the strength of the amplifier signal and the distance that the LoRa can reach. By utilizing the frequency of the LoRa, it is expected to monitor the load current and voltage generated by electronic equipment in the ferry passenger's passenger space. From the monitoring tool obtained the test results of testing Television with power 27 W and Voltage 19 Volt obtained the percentage of voltage error is 1.09 % and the percentage of current error is 1.15 %.3. Based on the results of the test data, it can be concluded that the current, voltage in the passenger room of the JokoTole KMP ship is fluctuating. This needs to be done monitoring the current load on the ship, especially in the safety alarm system, electronic de-vices, pumps for the safety of shipping, which at KMP Joko Tole still uses con-ventional technology and the absence of adequate electrical system data sup-port.